Late-outburst radio flaring in SS Cyg and evidence for a powerful kinetic output channel in cataclysmic variables - Fender, R; Bright, J; Mooley, K; Miller-Jones, J (Oxford University Press, 2019)
Accreting white dwarfs in binary systems known as cataclysmic variables (CVs) have in recent years been shown to produce radio flares during outbursts, qualitatively similar to those observed from neutron star and black hole X-ray binaries, but their ubiquity and energetic significance for the accretion flow has remained uncertain. We present new radio observations of the CV SS Cyg with Arcminute Microkelvin Imager Large Array, which show for the second time late-ouburst radio flaring, in 2016 April. This flaring occurs during the optical flux decay phase, about 10 d after the well-established early-time radio flaring. We infer that both the early- and late-outburst flares are a common feature of the radio outbursts of SS Cyg, albeit of variable amplitudes, and probably of all dwarf novae. We furthermore present new analysis of the physical conditions in the best-sampled late-outburst flare, from 2016 February, which showed clear optical depth evolution. From this we can infer that the synchrotron-emitting plasma was expanding at about 1 per cent of the speed of light, and at peak had a magnetic field of order 1 G and total energy content ≥10 erg. While this result is independent of the geometry of the synchrotron-emitting region, the most likely origin is in a jet carrying away a significant amount of the available accretion power. 33